"We've Bought a Tens Machine and We're Trying Aromatherapy and Hypnobirthing": Being Prepared for Labour and Birth?. Issue 1 (8th December 2020) - Miller, Tina
This commentary is written to mark 10 years of comprehensive maternal scholarship undertaken across the Journal. In this piece I return to reflect on the gap between women's anticipations of labour and birth and their experiences, as births appear to be becoming more interventionist. This leads me to invite a debate about why this might be and whether it matters?